The Mental Welfare Commission for Scotland – a unique and influential voice. (14th December 2015) - McKay, Colin; Welsh, Heather
Abstract : Purpose: – The purpose of this paper is to describe the unique and independent role of the Mental Welfare Commission for Scotland. Design/methodology/approach: – The paper takes the reader through the history of the Commission, its changing status, roles and responsibilities, its influence and impact, and current priorities. It is based on details of the Commission ' s development, narrative from current employees and published investigations and advice. Findings: – The Mental Welfare Commission has advanced significantly since its original establishment. It plays a vital role in protecting the human rights of people in Scotland with learning disabilities and mental illness, by visiting those who are in receipt of care or treatment, investigating situations of concern, providing advice and guidance, monitoring the Mental Health (Care and Treatment) (Scotland) Act 2003 and Adults with Incapacity (Scotland) Act 2000 and shaping relevant policy and legislation. Originality/value: – This paper provides an introduction to the work of the Commission, which will be of value to readers in Scotland and beyond. It illustrates its importance in preserving the rights of individuals with learning disabilities and mental illness in line with the UN Convention on the Rights of Persons with Disabilities and other legislation.